Policy and financing—why is sea transport currently invisible in the search for a low carbon future for Pacific Island Countries? - Nuttall, Peter R.; Newell, Alison; Bola, Amelia; Kaitu'u, John; Prasad, Biman (Frontiers in Marine Science, 2014)
The role of financing and policy in research, development, trialing and introduction of renewable energy technologies in the Pacific maritime sector is considered. Key research and trials of renewable energy technologies for sea transport in the Pacific from the 1980s and the critical role played by agencies such as the United Nations in leveraging support from funders such as the Asian Development Bank and European Union are reviewed. The lack of current policy on potential renewable energy technology use in sea transport at national, regional, and development agency levels is discussed with the Asian Development Bank used as a case study. The urgent need for such technology to be commercially trialed as a means of reducing the region's dependency on fossil fuels given the importance of sea transport to socio-economic development in the Pacific is outlined in light of the proportion of fossil fuel currently used by the maritime sector. The paper concludes that review of current funding strategies and policies to include both sea transport and the potential for use of renewable energy technologies in the maritime sector in the Pacific is a priority and current reliance on the private sector acting alone needs review.